2006
DOI: 10.1111/j.1748-5827.2006.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a peripherally administered three‐in‐one parenteral nutrition product in dogs

Abstract: Using the product for 24 hours/day may require catheter replacement due to line failure. Other than line failure, which may be improved by 10- to 12-hour infusion times, this product was found to be safe and practical for short-term peripheral parenteral nutrition in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…[25][26][27] Studies evaluating the use of PN solutions in clinical veterinary patients are limited; however, the most recent studies similarly concluded that the most common metabolic complication associated with PN was hyperglycemia. 3,17,[28][29][30] In the current study, 4 of 36 patients with normal glucose values prior to Pro-calAmine infusion developed hyperglycemia following administration of this PPN solution. The clinical significance of this finding is questionable, however, as these dogs exhibited mild hyperglycemia (< 9.9 mmol/L [180 mg/dL]) that did not prompt clinical intervention.…”
Section: Discussionmentioning
confidence: 59%
“…[25][26][27] Studies evaluating the use of PN solutions in clinical veterinary patients are limited; however, the most recent studies similarly concluded that the most common metabolic complication associated with PN was hyperglycemia. 3,17,[28][29][30] In the current study, 4 of 36 patients with normal glucose values prior to Pro-calAmine infusion developed hyperglycemia following administration of this PPN solution. The clinical significance of this finding is questionable, however, as these dogs exhibited mild hyperglycemia (< 9.9 mmol/L [180 mg/dL]) that did not prompt clinical intervention.…”
Section: Discussionmentioning
confidence: 59%
“…For example, 15% of neonatal foals given a lipid‐rich emulsion suffered a thrombotic complication in 1 study . In a study in dogs, the median time to severe mechanical complications or outright failure of the PN administration line due to thrombosis or apparent thrombophlebitis, inferred from clinical observations of swelling or redness of the leg, was 36 hours . In another study, mechanical complications occurred in 25% (81/319) dogs given PN.…”
Section: Introductionmentioning
confidence: 99%
“…21 The goal with this form of PN is to supply a portion of the daily caloric requirements through a peripheral line without inducing thrombophlebitis secondary to excessive hypertonicity. Peripheral PN-as noted, also commonly abbreviated PPN-has been utilized (MacEntire D: Personal communication, 2009) and evaluated clinically in dogs.…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…Peripheral PN-as noted, also commonly abbreviated PPN-has been utilized (MacEntire D: Personal communication, 2009) and evaluated clinically in dogs. 21 This solution, which has higher osmolarity, caloric density (0.63 kcal/mL), and amino acid concentration than the "custom" solution described further on, was administered to dogs at 2 mL/kg/hour. Administration of such solutions has been shown to improve nitrogen balance.…”
Section: Parenteral Nutritionmentioning
confidence: 99%